Analisis Kebijakan Pengelolaan Institusional Repositori Perpustakaan Universitas Medan Area - Hannum Angginami; Retno Sayekti; Muslih Fathurrahman (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research concerns the Institutional Management Policy of the Medan Area University Library Repository.The purpose of this research is to find out how the institutional management policy of the repository in the Medan Area University library. This research is a descriptive study using a qualitative approach, datacollection techniques with observation, interviews and documentation. The results of this study indicate that the background of the Institutional Repository in the Medan Area University Library is an effort to optimize library tasks in collecting, storing, managing, organizing, preserving, and distributing scientific work information, especially within the Medan Area University academic community. The institutional goal of the repository for the Medan Area University library is to collect (collect), manage, preserve, and open access (distribute) all intellectual works produced by the UMA academic community, both students, lecturers, and staff. The institutional management strategy for the Medan Area University library repository all librarians and employees at the Medan Area University library are involved in repository management, because little or not all human resources (HR) are involved, the library also carries out promotions by conducting outreach to students and also promotion through social media such as ig and fb, building library repositories using hardware (hardware) such as computers and software (software) made by outside developers, preserving library collections Medan Area University library providing external hard drives from CDs that have been given by students to the library then copied to an external hard drive.